Briarenolides M–T, new briarane diterpenoids from a Formosan octocoral Briareum sp. Issue 7 (18th February 2016) - Su, Yin-Di; Wen, Zhi-Hong; Wu, Yang-Chang; Fang, Lee-Shing; Chen, Yu-Hsin; Chang, Yu-Chia; Sheu, Jyh-Horng; Sung, Ping-Jyun
Abstract: Eight new briarane diterpenoids, designated briarenolides M–T (1 –8 ), were isolated from an octocoral identified as Briareum sp. The structures of briaranes1 –8 were established by spectroscopic methods and by comparison of the spectroscopic data with those of known analogues. The relationship between 1 H and 13 C NMR chemical shifts of 2-hydroxybriaranes possessing of (A) a Δ 3, 5(16) -conjugated diene moiety or (B) a Δ 3, 5 -conjugated diene moiety are described. Briarenolides M (1 ), P (4 ), S (7 ), and T (8 ) were found to inhibit the accumulation of the pro-inflammatory inducible nitric oxide synthase (iNOS) protein and briarenolides N (2 ), P (4 ), and T (8 ) were found to inhibit the accumulation of the pro-inflammatory cyclooxygenase-2 (COX-2) protein in LPS (lipopolysaccharide)-stimulated RAW264.7 macrophage cells. Graphical abstract: